Physics ContributionsA survey of quality control practices for high dose rate (HDR) and pulsed dose rate (PDR) brachytherapy in the United Kingdom - Palmer, Antony L.; Bidmead, Margaret; Nisbet, Andrew (Journal of Contemporary Brachytherapy, 2012)
Purpose: A survey of quality control (QC) currently undertaken in UK radiotherapy centres for high dose rate (HDR) and pulsed dose rate (PDR) brachytherapy has been conducted. The purpose was to benchmark current accepted practice of tests, frequencies and tolerances to assure acceptable HDR/PDR equipment performance. It is 20 years since a similar survey was conducted in the UK and the current review is timed to coincide with a revision of the IPEM Report 81 guidelines for quality control in radiotherapy. Material and methods : All radiotherapy centres in the UK were invited by email to complete a comprehensive questionnaire on their current brachytherapy QC practice, including: equipment type, patient workload, source calibration method, level of image guidance for planning, prescribing practices, QC tests, method used, staff involved, test frequencies, and acceptable tolerance limits. Results: Survey data was acquired between June and August 2012. Of the 64 centres invited, 47 (73%) responded, with 31 centres having brachytherapy equipment (3 PDR) and fully completing the survey, 13 reporting no HDR/PDR brachytherapy, and 3 intending to commence HDR brachytherapy in the near future. All centres had comprehensive QC schedules in place and there was general agreement on key test frequencies and tolerances. Greatest discord was whether source strength for treatment planning should be derived from measurement, as at 58% of centres, or from the certified value, at 42%. IPEM Report 81 continues to be the most frequently cited source of QC guidance, followed by ESTRO Booklet No. 8. Conclusions : A comprehensive survey of QC practices for HDR/PDR brachytherapy in UK has been conducted. This is a useful reference to which centres may benchmark their own practice. However, individuals should take a risk-assessment based approach, employing full knowledge of local equipment, clinical procedures and available test equipment in order to determine individual QC needs.